Les manifestes dadaïstes et l’art de la répétition ou comment “dire” qu’on n’a rien à dire - Toma, Iulian (Anales de Filología Francesa, 2023)
This article examines one of the major roles played by repetition in the Dadaist manifestos. While the goal of a manifesto, by definition, is to convey a message, the Dadaist manifestos suggest, through the use of the repetition, that they have no intention of proposing or communicating anything. Radically self-referential, this type of repetition, as demonstrated in this article analyzing several texts by Hugo Ball, André Breton, Francis Picabia, Georges Ribemont-Dessaignes, Tristan Tzara, Louis Aragon…, reflects Dada’s nihilistic program.